Oral artesunate in the treatment of uncomplicated hyperparasitemic falciparum malaria. - Luxemburger, C; Nosten, F; Raimond, S; Chongsuphajaisiddhi, T; White, N (1995)
Patients with uncomplicated hyperparasitemic falciparum malaria are usually given parenteral antimalarial treatment to prevent a progression to vital organ dysfunction and death. Since the oral artemisinin derivatives are more rapidly effective than other antimalarial drugs, we compared oral artesunate (4 mg/kg/day for three days with mefloquine 25 mg/kg on the second day) with an intravenous quinine loading dose (20 mg of salt/kg initially then 10 mg/kg every 8 hr, followed by mefloquine 25 mg/kg) in an open paired randomized trial in 60 patients with acute falciparum malaria and greater than 4% parasitemia, but no evidence of vital organ dysfunction. There were no deaths and none of the patients progressed to develop severe malaria. Oral artesunate treatment resulted in shorter median [range] times to fever clearance (19 hr [4-45] versus 47 hr [4-107]) (P < 0.0001), parasite clearance (36 hr [18-61] versus 82 hr [36-104]) (P < 0.0001), and discharge from the hospital (25 hr [12-44] versus 58 hr [24-115]) (P < 0.0001). There was no toxicity attributable to artesunate. The cure rates by day 28 were 70% (19 of 27) and 39% (11 of 27) in the artesunate and quinine groups, respectively (relative risk = 1.7; 95% confidence interval = 1.0-3.0). Oral artesunate was simpler, cheaper, safer, and more effective than intravenous quinine for the treatment of uncomplicated hyperparasitemia.